2017
DOI: 10.1111/hex.12532
|View full text |Cite
|
Sign up to set email alerts
|

“It goes against the grain”: A qualitative study of the experiences of parents’ administering distressing health‐care procedures for their child at home

Abstract: BackgroundParents caring for children with complex and long‐term conditions at home take on responsibility for technical health‐care procedures that may cause their child distress. Little evidence exists about parents’ experience of this specific aspect of their caring role.AimsTo explore and understand parents’ experiences of administering distressing health‐care procedures as part of caring for their child at home.DesignAn explorative qualitative study.MethodsA purposive sample of parents who were currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Contrary to our hypotheses, we did not see significant correlations between anxiety, depression and the HCEI measures; this may be that healthcare engagement and tolerance for uncertainty are more outward-oriented than coping self-efficacy and the parents may feel the need to focus on these despite their inner emotional state. Parenting children with complex medical needs, with or without a diagnosis, frequently requires the parent to learn about and provide medical interventions, act as a care coordinator, and be an advocate for their child (Cady & Belew, 2017; Spiers & Beresford, 2017) and parents in our study who are actively engaged in their children’s healthcare are reflective of this process.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our hypotheses, we did not see significant correlations between anxiety, depression and the HCEI measures; this may be that healthcare engagement and tolerance for uncertainty are more outward-oriented than coping self-efficacy and the parents may feel the need to focus on these despite their inner emotional state. Parenting children with complex medical needs, with or without a diagnosis, frequently requires the parent to learn about and provide medical interventions, act as a care coordinator, and be an advocate for their child (Cady & Belew, 2017; Spiers & Beresford, 2017) and parents in our study who are actively engaged in their children’s healthcare are reflective of this process.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lot to learn and many of the medical procedures parents undertake are emotionally demanding. 7,8 Studies have described the tension some parents feel between their role as a 'nurse' and as a parent. 9 These parents experience significantly more stress than caregivers of healthy children, with increased stress associated with greater parental responsibility for treatment management.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found evidence of safety concerns in the practices of some family carers 16–18. Many families also worry about making mistakes or feel inadequately prepared 29 30. The adequacy of training and information for parents needs to be viewed as a system issue and vital to the safety of care at home 31…”
Section: Discussionmentioning
confidence: 99%